Tobacco advertising ban discourse in online media coverage - Samodro, Dewanto (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: One industry that allocates quite a lot of budgets for advertising is the tobacco industries, which is still allowed with restrictions. Along with efforts to protect the public from negative exposure to tobacco products, tobacco control activists are discussing a total ban on tobacco advertisement in various media. The campaign to voice a total ban on tobacco advertisement has also reported in online media coverage. The purpose of this study is to determine the frame of online media coverage of the tobacco advertisement ban discourse. Methods: This research analyzed online media news stories in January – April 2022 period about the discourse on the tobacco advertising ban using framing analysis method with a qualitative approach. This study analyzes the frame of online media news stories related to the discourse of a total ban on tobacco advertisement. Results: This research found that there were two tones of news story in online media about the discourse of tobacco advertising ban, namely those that supported and those that rejected. News story with a supportive tone usually took source person from the civil society groups that support tobacco control, while news story with a rejection tone usually placed the tobacco industries as a disadvantaged party which in the end also harmed the workers and tobacco farmers. Conclusion: The discourse of tobacco advertisement ban was framed in different way by online media. There are at least two different tones in media coverage of the discourse, namely those that support the tobacco advertisement ban and those who reject the tobacco advertisement ban, although more news was found to be supportive.